2016
DOI: 10.1177/1352458516682103
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of decision-making in multiple sclerosis: A neuroeconomic approach

Abstract: Objective To assess the decision-making impairment in patients with multiple sclerosis (MS) and how they relate to other cognitive domains. Methods We performed a crossectional analysis in 84 patients with MS and 21 matched healthy controls using four tasks taken from behavioral economics: 1) risk preferences, 2) choice consistency, 3) delay of gratification, and 4) rate of learning. All tasks were conducted using real-world reward outcomes (food or money) in different real-life conditions. Participants unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Consistent with the findings in Sepúlveda et al. 4 and Muhlert et al., 5 this analysis showed that heightened impulsivity is not contributing to worse DM-learning in severe MS because the groups did not differ. Finally, in another supplementary analysis of behavioral DM, we tested the link of DM-learning and clinical parameters but, however, failed to reveal such associations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with the findings in Sepúlveda et al. 4 and Muhlert et al., 5 this analysis showed that heightened impulsivity is not contributing to worse DM-learning in severe MS because the groups did not differ. Finally, in another supplementary analysis of behavioral DM, we tested the link of DM-learning and clinical parameters but, however, failed to reveal such associations.…”
Section: Discussionsupporting
confidence: 88%
“…2,3 Among cognitive deficits, impaired decision-making (DM; the ability to choose between alternatives) was found. 49 DM performance in MS deteriorates across the disease course 7,9 although it is not exactly known when this process begins. Some authors argue that it already starts in early MS stages, 4,6 whereas other authors found evidence for impaired DM in later stages only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, delayed reward collection along with the slower rates of image touches (Figure 3B) are in agreement with decreased reward anticipation, reduced learning from rewards and psychomotor slowing in individuals with schizophrenia 73 . At the same time, these signs are also in accord with decreased responsiveness to rewards, slower reaction time and reduced processing speed in decision‐making tasks in individuals with MS 21,74‐76 . Touchscreen CANTAB tasks ‘Match to Sample’, ‘Paired Associates Learning’ and ‘Spatial Working Memory’ have revealed deficits in multiple cognitive domains in MS patients, including impairments in processing speed, reaction time, attention and executive function 20 .…”
Section: Discussionsupporting
confidence: 58%
“…It is a necessary ability for adequate functioning, and is often impaired in patients with psychiatric disorders such as schizophrenia, 1 obsessive-compulsive disorder, 2,3 bipolar disorder (BD) 4 and depression, 5 and neurological disorders such as multiple sclerosis 6 and traumatic brain injury. 7 Recent studies have also identified it as a significant predictor of clinical outcomes such as treatment dropout and relapse in substance disorders 8,9 and future substance use in patients with BD.…”
Section: Introductionmentioning
confidence: 99%